2020
DOI: 10.1016/j.heliyon.2020.e05037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of teenage pregnancy and the associated contextual correlates in Rwanda

Abstract: The rate of teenage pregnancy remains unacceptably high in most developing countries. In Rwanda, studies show a rapid increase over the past two decades despite the political achievements of women's empowerment, and efforts to curtail child sexual abuse. Unfortunately, the current knowledge of the household determinants of teenage pregnancies in Rwanda is limited, as recent studies have focused on providing numbers with little analysis of proximate causal factors or focused on the individual determinants. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 16 publications
4
25
1
3
Order By: Relevance
“…While both older and younger ages have been identified as predictors of late ANC initiation in other studies, we found that younger participants were more likely to delay ANC-1 in our cohort [ 17 , 41 , 42 ]. Various factors may be at play, including the stigma and social isolation associated with teenage pregnancy [ 43 ]. Our results suggest that targeting adolescents and those with lower educational attainment may be particularly high-yield in improving rates of early ANC attendance and should be a priority for CHW outreach efforts.…”
Section: Discussionmentioning
confidence: 99%
“…While both older and younger ages have been identified as predictors of late ANC initiation in other studies, we found that younger participants were more likely to delay ANC-1 in our cohort [ 17 , 41 , 42 ]. Various factors may be at play, including the stigma and social isolation associated with teenage pregnancy [ 43 ]. Our results suggest that targeting adolescents and those with lower educational attainment may be particularly high-yield in improving rates of early ANC attendance and should be a priority for CHW outreach efforts.…”
Section: Discussionmentioning
confidence: 99%
“…The Rwandan evidence base on adolescents, contraceptive use and services is more extensive, reflecting secondary analyses of Demographic and Health Survey data (Hakizimana et al 2019;Uwizeye et al 2020). A regional comparison of young women's (15-24 years) contraceptive use shows how Rwanda lags significantly behind its neighbours, despite increases in contraceptive use over the last twenty years (Dennis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that the larger the family size, the greater the risk of teenage pregnancy, consistent with the findings from previous literature [ 27 , 28 ]. In Rwanda, large families (with more than 10 family members) were more than two times likely to have pregnant teenage adolescents compared with smaller households (OR = 2.13, 95% CI = 1.99–4.57) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%